Salivary Interleukin-6 Levels among Polycystic Ovary Syndrome (Pcos) Patients with and Without Chronic Periodontitis - A Comparitive Study - Varghese, Dr. Arun; Christy, Dr. A. Julie; Pratheeba, Dr. B.; Saraswathy, Dr. P.; Ravi, Dr. Sumathy (International Journal of Innovative Research in Medical Science, 2019)
Background: Periodontitis is associates with various systemic disease one of which is PCOS. PCOS is a genetically complex endocrinopathy of uncertain etiology affecting women of reproductive age group which results in most common cause of anovulatory infertility, menstrual dysfunction and hirsutism. PCOS have close association with cardiometabolic risk profile, insulin resistance (IR), hyperinsulinemia, central obesity, dyslipidemia and increase prevalence of cardiovascular risk factors. The common pathway is the chronic low grade inflammation which is constituted by proinflammatory cytokine IL-6. Aim: To compare salivary IL-6 levels among patients with Polycystic ovary syndrome (PCOS) patients with chronic periodontitis and without Chronic Periodontitis. Materials and Methods: Newly diagnosed PCOS patients were selected for the study and the periodontal Parameters were recorded. Group A consist of 42 patients of PCOS with Periodontitis & Group B consist of 42 patients of PCOS without Periodontitis. Salivary levels of IL-6 was compared between the two groups, and was assessed by Enzyme Linked Immuno Sorbent Assay (ELISA) kit (Bioassay). Results: BOP in group A was 1.40 ± 0.40 and in group B it was 0.91.± 0.18,PPD in group A was 4.23 ± 0.134 and in group B it was 1.30 ± 0.06, CAL in group A was 4.87 ± 0.124 and in group B was 1.30 ± 0.06, CAL in group A was 4.87 ± 0.124 and in group B was 1.30 ± 0.06. The values were statistically significant (p= <.001). IL-6 level in group A is 102.59 ± 18.2 and in group B it was 51.3 ± 25.3. Which implies there is an increase salivary IL-6 level in group A (PCOS with Periodontitis) than group B (PCOS without Periodontitis). Conclusion: Salivary IL-6 levels shows a double fold increase in Group A (PCOS with Periodontitis) than in group B ( PCOS without Periodontitis).